Social and ethical criteria for prioritizing patients: A survey of students and health professionals in Portugal. - Pinho, Micaela (2016)
This qualitative/quantitative study examines the ethical dilemma of microallocation of health resources. It seeks to identify and compare the opinion of two groups in Portuguese society – students and health professionals – on the importance of personal characteristics of patients at the moment of prioritizing them and if the choices can be explained by bioethical references of a utilitarian or deontological nature. Data were collected by means of a questionnaire administered to a sample of 180 students and 60 health professionals. Faced with hypothetical emergency scenarios, the respondents had to choose between two patients (distinguished by: age, gender, social responsibility, economic and employment situation, harmful health behaviors and criminal record), duly selecting who to treat and then justifying their choice. The results suggest the existence of differences in choices between the two groups, with health professionals revealing they are less prepared to accept the use of social criteria in a context of scarce resources and co-existence of utilitarian and deontological criteria, with a predominance of efficiency on the part of health professionals and equity on the part of students.